An Innovative Approach for Increasing Access to Over-the-Counter Hearing Aids in Rural Communities of Alabama - Hay-McCutcheon, Marcia J.; Berenbrok, Lucas A.; Mormer, Elaine; Hughes, Peter J. (Seminars in Hearing, 2025)
Adults living in rural communities of Alabama have limited or no access to hearing healthcare for a variety of reasons. Hearing loss can result in decreased social contact, potentially leading to loneliness, and it has been associated with depression and cognitive decline. To improve access to hearing healthcare, the FDA released its Final Rule in 2022 stating that adults with perceived mild-to-moderate hearing loss can purchase over-the-counter hearing aids (OTC HAs) on their own without clearance from a physician or through the care of an audiologist. Current research suggests, however, that adults benefit from professional support when purchasing and setting their OTC HAs. Understanding how much support is needed and how to best provide the support will be necessary for successful OTC HA use. Considering that these devices can now be purchased at pharmacies, one model in rural areas could involve the pharmacy technician who could assist and support those with hearing loss in community pharmacies. This article outlines a pharmacy technician educational training program that will incorporate didactic, interactional, and experiential learning components to promote the use of OTC HAs. The outcomes from this project will provide the foundation for the development and implementation of one model for improving access to hearing healthcare in rural communities.
Keywords: community pharmacy service; continuing pharmacy education; hearing loss; rural health services